Molecular Basis of Zinc-Dependent Endocytosis of Human ZIP4 Transceptor - Zhang, Chi (Cell Rep, 2020)
Nutrient transporters can be rapidly removed from the cell surface via substrate-stimulated endocytosis as a way to control nutrient influx, but the molecular underpinnings are not well understood. In this work, we focus on zinc-dependent endocytosis of human ZIP4 (hZIP4), a zinc transporter that is essential for dietary zinc uptake. Structure-guided mutagenesis and internalization assay reveal that hZIP4 per se acts as the exclusive zinc sensor, with the transport site’s being responsible for zinc sensing. In an effort of seeking sorting signal, a scan of the longest cytosolic loop (L2) leads to identification of a conserved Leu-Gln-Leu motif that is essential for endocytosis. Partial proteolysis of purified hZIP4 demonstrates a structural coupling between the transport site and the L2 upon zinc binding, which supports a working model of how zinc ions at physiological concentration trigger a conformation-dependent endocytosis of the zinc transporter. This work provides a paradigm on post-translational regulation of nutrient transporters.